Pengaruh Sistem Informasi dan Komunikasi terhadap Penerimaaan Teknologi dalam Pengembangan Desa Cerdas - Abung Supama Wijaya; Pudji Muljono; Amiruddin Saleh; Dwi Retno Hapsari (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
The utilization of Information and Communication Technology (ICT) is generally considered as a strategy to achieve goals in addressing development challenges and social changes faced by communities. The implementation of ICT in the development of Smart Villages is an effort to effectively utilize technology in order to enhance the quality of life and public services at the village level. The objective of this study is to analyze the influence of information systems on the acceptance of technology in the development of Smart Villages in Hanura Village, Teluk Pandan District, Pesawaran Regency, Lampung Province, and Kertayasa Village, Sindang Agung District, Kuningan Regency, West Java Province. The research is designed as a quantitative approach supported by qualitative data (mixed methods). The research sample consists of 194 individuals selected through purposive sampling. The data collected includes primary and secondary data. Primary data is gathered through interviews using a questionnaire guide and field observations. Data analysis involves descriptive statistical analysis and inferential statistical analysis using Structural Equation Modeling (SEM). The findings of the study indicate that information quality has a positive and significant influence on the perceived usefulness of ICT and the perceived ease of use of ICT. Service quality has a positive and significant influence on all three dimensions of technology acceptance. However, there is no significant influence between system quality and user satisfaction with ICT. These results highlight the importance of attention to the quality of information delivered and the quality of services provided in the development of Smart Villages to enhance the acceptance and benefits of ICT utilization in Smart Village development.